2011
DOI: 10.1097/fpc.0b013e328348c76b
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine metabolism and the significance of UGT1A448V and UGT2B1067Y variants

Abstract: Olanzapine (OLZ) is an antipsychotic used in the treatment of schizophrenia, bipolar disorder, and treatment-resistant depression. Glucuronidation via the UDP-glucuronosyltransferase (UGT) family of enzymes is the major mode of OLZ metabolism and polymorphisms in these enzymes could contribute to inter-individual variability in OLZ metabolism and therapeutic response. In a screening of cell lines over-expressing individual UGTs, only UGTs 1A4 and 2B10 exhibited glucuronidation activity against OLZ. The UGT1A42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 48 publications
(77 reference statements)
4
31
0
Order By: Relevance
“…Polymorphisms in the coding region of the UGT1A4 gene may alter enzyme activity and thereby lead to reduced or enhanced elimination of LTG and, thus, altered serum concentrations. Previous studies on the effects of two common SNPs of the UGT1A4 gene, *2 and *3, found both unchanged, reduced, and enhanced enzyme activity (Chang et al 2014;Ehmer et al 2004;Erickson-Ridout et al 2011, Under 12 years, n (%) 6 (3 %)…”
Section: Discussionmentioning
confidence: 94%
“…Polymorphisms in the coding region of the UGT1A4 gene may alter enzyme activity and thereby lead to reduced or enhanced elimination of LTG and, thus, altered serum concentrations. Previous studies on the effects of two common SNPs of the UGT1A4 gene, *2 and *3, found both unchanged, reduced, and enhanced enzyme activity (Chang et al 2014;Ehmer et al 2004;Erickson-Ridout et al 2011, Under 12 years, n (%) 6 (3 %)…”
Section: Discussionmentioning
confidence: 94%
“…Anastrozole glucuronidation was highly correlated with lamotrigine glucuronidation (a diagnostic substrate for UGT1A4; r = 0.99, P , 0.0001), 874 Edavana et al at ASPET Journals on May 11, 2018 dmd.aspetjournals.org but some recent studies suggest that lamotrigine may not be entirely specific for UGT1A4 (Erickson-Ridout et al, 2011). However, these results support the predominant (but not the sole) role of UGT1A4 in the direct glucuronidation of anastrozole.…”
Section: Downloaded Frommentioning
confidence: 92%
“…The 10-N-glucuronide is the most abundant metabolite. Glucuronidation by the UDP-glucuronosyltransferase family of enzymes (1A4 and 2B10) is the major mode of olanzapine metabolism, and polymorphisms in these enzymes could contribute to interindividual variability in olanzapine metabolism and therapeutic response (44). Studies have shown that mean plasma olanzapine concentrations vary widely, depending on factors such as the prescribed daily dose and the duration of treatment (41).…”
Section: Tdm Of Particular Atypical Antipsychotic Drugsmentioning
confidence: 99%